Detection of NFKB1 Gene in Patients with Type 2 Diabetes Mellitus and Non Diabetics Using Polymerase Chain Reaction Method - Priska Putri Cahyaningtyas; Fitria Diniah Janah Sayekti (Al-Hayat: Journal of Biology and Applied Biology, 2024)
A metabolic condition called type 2 diabetes mellitus is characterized by elevated blood sugar levels because of reduced insulin release by β pancreatic cells. The primary form of NF-kB is Nuclear Factor Kappa Beta subunit-1 (NFKB1), which is a gene that encodes the DNA binding protein (p50). The NFKB1 gene contributes to the oxidative stress and mild inflammatory processes that might exacerbate diabetes. The enzymatic procedure known as Polymerase Chain Reaction (PCR), multiplies a nucleotide sequence in order to identify if type 2 diabetes mellitus or non-diabetic has the NFKB1 gene. The purpose of this study was to detect the presence of the NFKB1 gene in type 2 diabetes mellitus and non-diabetes. The study used a descriptive research method using a purposive sampling technique conducted at the molecular biology laboratory of the Sekolah Tinggi Ilmu Kesehatan Nasional. The respondents in this study were 9 patients with type 2 diabetes mellitus who were prolanes of Puskesmas Wonosari I Klaten and 9 non-diabetic patients in PKK Kadilangu RT 2/RW 1, Baki, Sukoharjo. From the results of the study, it can be seen that the NFKB1 gene was detected after electrophoresis and visualized at 176 bp (base pair). The qualitative presence of the NFKB1 gene in DNA is still detectable, but the level of gene expression in the soil of transcription and translation is not yet known.